SIMULIIDAE (DIPTERA) FROM QUEQUÉN GRANDE RIVER AT LAS CASCADAS (BUENOS AIRES, ARGENTINA): POPULATION VARIATION AND RELATIONSHIP W ITH TEM PERATURE, STREAM DISCHARGE AND PRECIPITATIONS (Acta Entomológica Chilena, 2022)
Quequén Grande is a river plain of the Southern area of Buenos Aires province; the river source is in theTandilia mountain system and has a permanent flow. The area has a températe climate and rains are more orless uniformly distributed all over the year. Black fly larvae and pupae were sampled mostly biweekly during26 monlhs at Las Cascadas area, about 15 km North Necochea city. Two species, Simulium (Psaroniocompsá)bonaerense Coscaron & Wygodzinsky and S. (Thyrsopelma) orbitale Lutz, were found. The former wasmore abundant and was present all along the year. Immatures density of S. bonaerense do not show correlation with temperature, precipitation or stream discharge. S. orbitale shows negative correlation with temperature.